O reflexo da pesquisa agrícola realizada pelas cooperativas do Paraná na produtividade da soja nos municípios de atuação - Silva, Márcio Leandro da (2019)
This paper analyzes the impact of the cooperatives agricultural research on the soybean productivity in the cities of Paraná where they operate. The research highlights the reflections of the agricultural research and development (R&D) made by the paranaense agricultural cooperatives on soybean culture taking into account that the state of Paraná is the second largest producer in Brazil, which, on the global stage, is the second largest producer. The methodology was comprised by bibliographic research, followed by a documentary analysis. Quantitative information was collected in five agroindustry cooperatives of Paraná and the findings were analyzed comparatively, using a multiple case study. Semi structured interviews were applied to managers and/or for those in charge of cooperative research and, through the content analysis method, the perceptions were structured and analyzed, contributing to the findings. The outcome shows that cooperatives investing in structured research activities have higher productivity indices, when compared to the average of the municipalities where they are located: in Paraná, Southern Region and Brazil. Based on the Spearman's correlation coefficient, it is affirmed that there is a high positive correlation between the variables soybean average productivity, with budgets dedicated to agricultural research. Thus, the common lines of research between the foundations and research centers of cooperatives are: agrometeorology, phytopathology, plant science, entomology, herbology, soil and plant nutrition, as well as environmental research. In the managers and technical staff point of view, technical recommendations, regionalization of research and product validation are the main contributions of Agricultural R&D to innovation in agribusiness. Therefore, it is suggested, as future research, to extend research to public research institutions and capital companies, economic and financial feasibility studies, as well as public-private partnerships.